Environmental pollution by wastewater from brown coal processing ¬ a remediation case study in Germany - Wiessner, Arndt; Müller, Jochen A.; Kuschk, Peter; Kappelmeyer, Uwe; Kästner, Matthias; Liu, Yong-Jun; Stottmeister, Ulrich (Journal of Environmental Engineering and Landscape Management, 2014)
The large scale of the contamination by the former carbo-chemical industry in Germany requires new and often interdisciplinary approaches for performing an economically sustainable remediation. For example, a highly toxic and dark-colored phenolic wastewater from a lignite pyrolysis factory was filled into a former open-cast pit, forming a large wastewater disposal pond. This caused an extensive environmental pollution, calling for an ecologically and economically acceptable strategy for remediation. Laboratory-scale investigations and pilot-scale tests were carried out. The result was the development of a strategy for an implementation of full-scale enhanced in situ natural attenuation on the basis of separate habitats in a meromictic pond. Long-term monitoring of the chemical and biological dynamics of the pond demonstrates the metamorphosis of a former highly polluted industrial waste deposition into a nature-integrated ecosystem with reduced danger for the environment, and confirmed the strategy for the chosen remediation management.